LIMBAH KULIT SINGKONG (MANIHOT ESCULENTA L.): ALTERNATIF OLAHAN MAKANAN SEHAT - Zephisius Rudiyanto Eso Ntelok (PGSD UNIKA SANTU PAULUS RUTENG, 2017)
Cassava is a plant that has many benefits, one of which is the staple food after rice. But unfortunately the cassava maximum potential has not been fully utilized, one of them is the cassava peel. Regarding the production of cassava in Indonesia reached 21 million tons in 2015 with the peel has its share of 20% of each kilogram of cassava roots, then there are approximately 4 million tons of cassava peel turns into waste. The aims of this community service programs is to provide knowledge and training to communities, how to process the waste of cassava peel into healthy and safe groceries to eat. The method used in this activity is made in two phases: first is to identify problems and socializing in the target area as well as the implementation stages of how to processing the waste of cassava peel iinto healthy groceries. After processing the results obtained are cassava peel waste can be processed into snacks that are healthy and safe for human consumption.